KESENJANGAN ANTARA ACUAN YURIDIS NORMATIF DAN KENYATAAN SOSIAL DALAM PERLINDUNGAN HUKUM TERHADAP PEKERJA MIGRAN - Rr Ani Wijayati (to-ra, 2015)
Legal protection of migrant workers in Indonesia are spread in many legal instrument including national laws, international convention and diplomatic agreements but there is not law or regulation that specifically regulates and recognizes the existence of formal implement homework that implicates protect.UU.No.39 Tahun 2004 was not sufficient to provide protection and acces.At the level of policy or implementation of this legislation is positioned migrant workers as a commodity in the form of provision of cheap labor for employers and not the protection of migrant workers Kata Kunci : Acuan yuridis, perlindungan hukum, buruh migran